SUMOylation inhibitors synergize with FXR agonists in combating liver fibrosis - Jiyu Zhou (Nature Portfolio, 2020)
FXR agonists have been investigated for the treatment of non-alcoholic steatohepatitis and liver fibrosis but the clinical efficacy is not optimal. Here the authors show that enhanced FXR SUMOylation in activated hepatic stellate cells reduces FXR signaling and that this can be rescued by SUMOylation inhibitors.